2013
DOI: 10.5194/nhessd-1-4635-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A coupling of hydrologic and hydraulic models appropriate for the fast floods of the Gardon river basin (France): results and comparisons with others modelling options

Abstract: Abstract. Mediterranean catchments are regularly affected by fast and flash floods. Numerous hydrologic models were developed, and allow to reconstruct these floods. However, these approaches often concern average size basins, of some hundreds km2. At more important scales (>1000 km2), a coupling of hydrologic and hydraulic models appears to be an adapted solution. This study analyses the performances of a coupling of models and compares them with those of others modelling strategies. The distributed SCS-LR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Consequently, such a relatively simple coupling strategy might affect model results, but the impacts of dynamic model feedback were assumed negligible when compared to the other sources of nontrivial uncertainty (e.g., the resolution and accuracy of the topographic data). Moreover, the use of dynamic coupling for the modeling of floodplain inundation dynamics at the large scale would require extremely large computational resources that hamper both the feasibility and transferability of the methodology to other study areas (Laganier et al, ; Lerat, ). Conversely, external unidirectional coupling has been successfully applied in a number of previous analyses (Bravo et al, ; Lian et al, ; Mejia & Reed, ), and it was hence considered a sensible approach for the purposes of this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, such a relatively simple coupling strategy might affect model results, but the impacts of dynamic model feedback were assumed negligible when compared to the other sources of nontrivial uncertainty (e.g., the resolution and accuracy of the topographic data). Moreover, the use of dynamic coupling for the modeling of floodplain inundation dynamics at the large scale would require extremely large computational resources that hamper both the feasibility and transferability of the methodology to other study areas (Laganier et al, ; Lerat, ). Conversely, external unidirectional coupling has been successfully applied in a number of previous analyses (Bravo et al, ; Lian et al, ; Mejia & Reed, ), and it was hence considered a sensible approach for the purposes of this study.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of using observed rainfall records as model input, Nam et al () used results from a numerical weather prediction model as input to the sequence of models for short‐term flood inundation prediction. Laganier et al (), Nguyen et al (), and Mai and De Smedt () showed that the coupled approach can adequately model flash floods and floodplain inundation. A coupled hydrologic‐hydraulic modeling approach was recommended by Grimaldi et al () for flood hazard modeling, by Felder et al () for probable maximum flood risk estimation, and by Sindhu and Durga () for flood damage mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…The coupling of Mike SHE (Système Hydrologique Européen, a distributed hydrological model) and Mike11 is a typical example of the coupling of the hydrologic and 1D hydrodynamic model [18,19]. The flow discharge rate obtained from the hydrologic model was treated as the mass source of the 1D hydrodynamic model, while the water depth calculated in the 1D hydrodynamic model was fed back to the hydrologic model [20]. However, as the 1D hydrodynamic model was employed in this coupling model, it could not provide enough 2D flood inundation information.…”
Section: Introductionmentioning
confidence: 99%